CURRICULUM AS A KEY INSTRUMENT TO AFRICAN RENAISSANCE AND SUBSEQUENT DEVELOPMENT: CHALLENGES AND THE WAY FORWARD - Billa, Lulu John; Makoge, Yvette Nyake (African Journal of Education and Practice, 2019)
Purpose: This study brings out the challenges faced by countries in the African continent in making curriculum an instrument for reinforcing African renaissance and subsequent multidimensional development of the continent. Therefore, the general focus of this review is on some of these challenges faced, and possible concrete policy and practical strategies of using curriculum (curricula) to reinforce African renaissance and subsequent development. Methods: The method employ to explore the objectives and questions of this paper is document analysis. . Question 1 examines the challenges faced by African countries in developing a curriculum (curricula) that will reinforce African renaissance and subsequent development; while question 2 examines the policies and practical strategies that can be put in place to make curriculum (curricula) a key reinforcement instrument to African Renaissance and subsequent development. The documents collected and analysed range within the following categories: 1. Official documents. 2. Research Studies and publications. Findings: Given that curriculum (curricula) determine what knowledge, skills and competences will be develop in individuals for their integration into the society and their contribution in the development of the society, makes curriculum (curricula) a force to reckon with as far as African Renaissance and subsequent development are concerned. However the curriculum of most African countries has experience a number of setbacks such as; Influence of neo-colonialism on education, insufficient expertise, sociocultural inferiority complex, and politization of economic studies which does to give room for most African countries to experience real and solid development. Unique Contribution to Theory, Policy and Practice: The study recommends that to viruses there are anti-viruses and in this case are the following policies and strategies; Curriculum revolution, creation of a national and pan-African Curriculum boards, Cultural Revolution oriented in pan Africanism, Industrial and entrepreneurial oriented curriculum (economic oriented curriculum). If Africans could come together, develop and implement these policies and strategies, then African Renaissance will cease from being a popular slogan and will become a reality and African development (socio-cultural, political and economic) will be lived not head in form of promises in powerful unrealistic speeches.